Landscapes preferences in the human species: insights for ethnobiology from evolutionary psychology - Moura, Joelson Moreno Brito; Ferreira Junior, Washington Soares; Silva, Taline Cristina; Albuquerque, Ulysses Paulino (Ethnobiology and Conservation, 2017)
According to evolutionary psychology, landscapes preferences by the human species are influenced by their evolutionary past. A set of psychological processes may have been selected to guide the selection of landscapes that offered advantages for the survival and reproduction of human groups in the past. In addition, these psychological mechanisms may also influence the current human behavior in landscapes preference. Based on this, Gordon Orians postulated the savanna hypothesis, which predicts that the human being prefers these environments, since in the past, African savanna environments had a set of important characteristics for survival. If this is true, there are important implications for ethnobiological studies that seek to understand the factors that can influence the selection and management of landscapes by human groups.